2010
DOI: 10.1128/jb.01426-09
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Klebsiella aerogenes Urease Accessory Protein UreD in Fusion with the Maltose Binding Protein

Abstract: Assembly of the Klebsiella aerogenes urease metallocenter requires four accessory proteins, UreD, UreE, UreF, and UreG, to effectively deliver and incorporate two Ni 2؉ ions into the nascent active site of the urease apoprotein (UreABC). Each accessory protein has been purified and characterized with the exception of UreD due to its insolubility when it is overproduced in recombinant cells. In this study, a translational fusion was made between the maltose binding protein (MBP) and UreD, with the resulting MBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
79
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(87 citation statements)
references
References 34 publications
7
79
0
1
Order By: Relevance
“…Due to the insolubility of UreD when it is overexpressed alone, there is no reported crystal structure of UreD and it is the least characterized of the urease accessory proteins. However, recently, investigators have found a maltose binding protein-UreD fusion to be soluble and useful in characterization studies (4). Consistent with previous reports, these investigators found UreD to bind both UreF and UreG in vivo.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Due to the insolubility of UreD when it is overexpressed alone, there is no reported crystal structure of UreD and it is the least characterized of the urease accessory proteins. However, recently, investigators have found a maltose binding protein-UreD fusion to be soluble and useful in characterization studies (4). Consistent with previous reports, these investigators found UreD to bind both UreF and UreG in vivo.…”
Section: Discussionsupporting
confidence: 77%
“…The total protein concentration in the lysates was determined using the Bio-Rad DC protein assay, according to the manufacturer's specifications and with bovine serum albumin as the standard. A lysate volume containing 50 g protein was combined with the phenol-hypochlorite assay buffer, consisting of 50 mM HEPES, pH 7.5, and 25 mM urea, and the mixture was compared to standards prepared from NH 4 Cl. E. coli MG1655 was used as a negative control, and EHEC O157:H7 strain IN1 and/or Mo28 was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…UreF was reported to form a complex with UreH(D) (9 -12), and the two proteins interact with UreG to form the heterotrimeric complex UreG-UreFUreH(D) (12,13). UreG is a SIMIBI (after signal recognition particle, MinD and BioD) class GTPase and is homologous to HypB, a hydrogenase maturation factor responsible for nickel delivery (14).…”
mentioning
confidence: 99%
“…Urease activation was inhibited by addition of the nonhydrolysable GTP analog, suggesting that GTPase activity of UreG is essential for urease activation (15). The apo-urease can form a complex with UreG-UreF-UreH(D) or its components of UreH(D) and UreF-UreH(D) (12,13,16,17). It has been shown that apo-urease can be activated in vitro by adding an excess amount of both carbon dioxide and nickel ion (18).…”
mentioning
confidence: 99%
“…To understand the activation mechanisms of ureases and the roles of accessory proteins in the posttranslational modifications of ureases, many different microbial nickel-containing ureases have been identified and characterized. Although the structural subunits and enzyme active sites have been well studied (3)(4)(5)(10)(11)(12)(13)(14)(15), the function of each accessory protein and the urease maturation mechanism are still poorly understood (3,4,(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%